Respuesta :

These are all abbreviated ways of writing a sum or product of functions.

[tex](f+g)(x) = f(x) + g(x)[/tex]

[tex](f\times g)(x) = f(x) \times g(x)[/tex]

Given [tex]f(x) = 2x+1[/tex] and [tex]g(x) = -3x-4[/tex], we have

a)

[tex](f+g)(x) = (2x+1) + (-3x-4) = (2x-3x) + (1-4) = \boxed{-x-3}[/tex]

b)

[tex](f-g)(x) = (2x+1) - (-3x-4) = (2x + 3x) + (1 + 4) = \boxed{5x+5}[/tex]

c) same as (b), but I bet you meant to use some other symbol. I'll just assume multiplication:

[tex](f\times g)(x) = (2x+1)\times(-3x-4) \\\\ = 2x\times(-3x)+1\times(-3x) +2x\times(-4) + 1\times(-4) \\\\ = -6x^2 - 3x - 8x - 4 \\\\ = \boxed{-6x^2 - 11x - 4}[/tex]

d)

[tex]\left(\dfrac fg\right)(x) = \dfrac{2x+1}{-3x-4} = \boxed{-\dfrac{2x+1}{3x+4}}[/tex]

though you could go on to simplify the quotient via long division; you would end up with the equivalent function (assuming x ≠ -4/3)

[tex]\left(\dfrac fg\right)(x) = -\dfrac{2x+1}{3x+4} = -\dfrac23 + \dfrac5{3(3x+4)}[/tex]

ACCESS MORE